Essential ingredients for radical innovations? The role of (un-)related variety and external linkages in Germany - Kolja Hesse; Dirk Fornahl (Papers in Regional Science, 2020)
The role of radical innovations for the economy has received increasing attention by German policy-makers. This paper investigates how (un-)related variety and external linkages influence these innovations in German labour market regions. Evidence is found that related and unrelated knowledge capabilities both support the emergence of radical innovations, although strong related capabilities are especially important. External linkages have an inverted u-shape relation to radically new ideas and can act as substitute for missing unrelated competences in a region. The results shed new light on the emergence of radical innovations and thus have interesting scientific and practical implications.
Keywords: 300; external linkages; labour market regions; radical innovations; related variety; unrelated variety